The Indicative Power of A Key Word System. A Quantitative Analysis of the Key Words in the Translation Studies Bibliography - Van Doorslaer, Luc (Meta, 2005)
AbstractOver the last decades, Translation Studies has explicitly tried to develop and regard itself as an interdiscipline. This evolution, as well as this self-esteem, has not only widened the focus of the field, it has also created a sometimes unclear eclecticism of topics, influences and methods. Characteristic of a still not too well-established and not always acknowledged discipline, research in Translation Studies has been looking for common interests and common grounds with other disciplines in an ambitious, but often unstructured way.The new online Translation Studies Bibliography (TSB - first release October 2004), which concentrates on the last decade, is used here as a tool for the analysis of the multiplicity of influences. Expanded several times a year, the TSB offers more than 7,000 annotated entries and uses a sophisticated key word system. The quantitative analysis of these key words and their thematic fields indicate the priorities in the dissemination of TS research over the past decade. How does research on translation today reflect this assumption? Is research on literary translation still as widespread as it was in the eighties? What is the relationship between publications on the ‘cultural turn’ and those on the ‘power turn’? The results of this analysis may indicate emphases and research priorities for the next decade in Translation Studies.